LEARNING MATERIAL ON THE LINEAR EQUATION SYSTEM WITH TWO VARIABLES (SPLDV) BY USING THE CONTEXT OF TRAIN TICKET RECEIPTS ON VIII GRADE STUDENTS - Amelia, Desy; Putri, Ratu Ilma Indra; Somakim, Somakim (Sriwijaya University Learning and Education International Conference, 2018)
This research aims to produce learning trajectory that can help students in learning material on the linear equation system with two variables (SPLDV). In this research, the method used design research. First stage, preparing for experiment. Second stage is the design experiment. The last stage is retrospective analysis. The learning approach used Indonesian Realistic Mathematics Education (PMRI). Subjects in this study were students of class VIII SMP Negeri 7 Palembang. In collecting the data, the researcher used observation, interview, video recording in classroom learning activities, collection of student work and collection of student test results. Hypothetical Learning Trajectory (HLT) is designed to compare with Actual Learning Trajectory (ALT) to analyze whether there is any difference between both of them. A retrospective analysis of SPLDV material learning shows that using the context of a train ticket receiptscan assist students in understanding SPLDV materials.